Safety profile and dose-dependent adverse events of upadacitinib in randomized clinical trials: a systematic review and meta-analysis - Zhang, Cong; Fu, Zhiwen; Liu, Jinmei; Li, Shijun; Chen, Xu; Zhang, Yi; Xie, Jiyi (Frontiers in Pharmacology, 2025)
IntroductionUpadacitinib, one of the Janus kinase (JAK) inhibitors, has gained global approval for treating various inflammatory and autoimmune diseases. However, despite the FDA’s black box warning on all JAK inhibitors, further research is necessary to verify the potential risks associated specifically with upadacitinib. Therefore, this study conducted a comprehensive systematic review and meta-analysis to assess the safety profile of upadacitinib and explore potential dose-related differences.MethodsRelevant English publications were identified through a comprehensive search of eligible databases conducted in March 2024 and subsequently updated in May 2025. The inclusion criteria focused on randomized controlled trials that included safety data on upadacitinib.ResultsA total of 9,547 patients were involved in this meta-analysis. Upadacitinib treatment was associated with an increased risk of hepatic disorder, neutropenia, acne, herpes zoster, and increased creatine phosphokinase levels. Notably, the risks of hepatic disorder, neutropenia, and acne also exhibited a dose-dependent relationship. However, there was no significant association between upadacitinib treatment and an elevated risk of renal dysfunction, non-melanoma skin cancer (NMSC), major adverse cardiovascular event (MACE), or venous thromboembolic event (VTE).ConclusionThis study reveals that upadacitinib generally has a favorable safety profile, with increased risks of hepatic disorder, neutropenia, acne, especially at higher doses. There was no significant association with renal dysfunction, NMSC, MACE, or VTE. These findings may serve as an evidence base for potential future modifications or removal of the FDA’s black box warning for upadacitinib.